Stress as a Mediator of Authentic Happiness and Learning Organization on the Work Performance of the Secretariat General Employees of the People's Consultative Assembly of the Republic of Indonesia (MPR-RI) - Manurung, Antonius Dieben Robinson (Dinasti Publisher, 2025)
This study aims to determine the effect of authentic happiness and learning organization on work performance, with stress as a mediator, on employees working at the MPR-RI General Staff Office. The research method used in this study is a quantitative method with a structural equation model (SEM). The study population was 201 people, with a saturated sampling technique, which means that the entire population can be a sample. Data analysis used in this study were: instrument quality test, descriptive analysis, structural model test, hypothesis test, and correlation matrix analysis between dimensions. The results of the study showed: 1) there is a positive and significant effect of authentic happiness on work performance; 2) there is a positive and significant effect of learning organization on work performance; 3) there is no positive and significant effect of authentic happiness on stress; 4) there is no positive and significant effect of learning organization on stress; 5) there is no positive and significant effect of stress on work performance; 6) there is no positive and significant effect of authentic happiness on work performance through stress as a mediator; 7) there is no positive and significant influence of learning organization on work performance through stress as a mediator in MPR RI employees; and 8) there is a positive and significant influence of authentic happiness and learning organization on work performance through stress with a fit model on empirical data, where the model fit index is obtained. The psychological implications of the results of this study reveal that the work performance of MPR RI secretariat employees will increase and be better by paying attention to the variables of authentic happiness and learning organization.